Temporal order of clinical and biomarker changes in familial frontotemporal dementia - Staffaroni, Adam M.; Quintana, Melanie; Wendelberger, Barbara; Heuer, Hilary W.; Russell, Lucy L.; Cobigo, Yann; Wolf, Amy; Petrucelli, Leonard; Gendron, Tania F.; Heller, Carolin; Clark, Annie L.; Taylor, Jack Carson; et al. (Nature Medicine, 2022)
Unlike familial Alzheimer’s disease, we have been unable to accurately predict symptom onset in presymptomatic familial frontotemporal dementia (f-FTD) mutation carriers, which is a major hurdle to designing disease prevention trials. We developed multimodal models for f-FTD disease progression and estimated clinical trial sample sizes in C9orf72 , GRN and MAPT mutation carriers. Models included longitudinal clinical and neuropsychological scores, regional brain volumes and plasma neurofilament light chain (NfL) in 796 carriers and 412 noncarrier controls. We found that the temporal ordering of clinical and biomarker progression differed by genotype. In prevention-trial simulations using model-based patient selection, atrophy and NfL were the best endpoints, whereas clinical measures were potential endpoints in early symptomatic trials. f-FTD prevention trials are feasible but will likely require global recruitment efforts. These disease progression models will facilitate the planning of f-FTD clinical trials, including the selection of optimal endpoints and enrollment criteria to maximize power to detect treatment effects. Empirically based models of disease progression in familial frontotemporal dementia reveal the relative ordering of clinical, neuroimaging, and fluid biomarker changes and facilitate novel clinical trial designs